A tainted trade? Moral ambivalence and legitimation work in the private security industry. - Thumala, A; Goold, B; Loader, I (2011)
The private security industry is often represented - and typically represents itself - as an expanding business, confident of its place in the world and sure of its ability to meet a rising demand for security. But closer inspection of the ways in which industry players talk about its past, present and future suggests that this self-promotion is accompanied by unease about the industry's condition and legitimacy. In this paper, we analyse the self-understandings of those who sell security - as revealed in interviews conducted with key industry players and in a range of trade materials - in order to highlight and dissect the constitutive elements of this ambivalence. This analysis begins by describing the reputational problems that are currently thought to beset the industry and the underlying fears about its status and worth that these difficulties disclose. We then examine how security players seek to legitimate the industry using various narratives of professionalization. Four such narratives are identified - regulation, education, association and borrowing - each of which seeks to justify private security and enhance the industry's social worth. What is striking about these legitimation claims is that they tend not to justify the selling of security in market terms. In conclusion we ask why this is the case and argue that market justifications are 'closed-off' by a moral ambivalence that attaches to an industry trading in products which cannot guarantee to deliver the condition that its consumers crave.